Vertigo as the First Sign of Chronic Myeloid Leukemia: A Case Report and Literature Review - Rubén Martín-Hernández; Diego Hernando Macías-Rodríguez; Víctor Martín-Sánchez; Cristina Cordero-Civantos; Santiago Santa Cruz-Ruiz; Ángel Batuecas-Caletrio (Case Reports in Otolaryngology)
Acute vestibular deficit as the first sign of leukemia is extremely rare. The literature shows some cases of sudden hearing loss accompanied by instability and associated with hyperviscosity syndrome. We present the case of a patient who presents a harmonic vestibular deficit of the right ear. The complementary studies revealed an abnormally high level of leukocytes. A peripheral blood cytogenetic analysis is performed due to a high suspicion of leukemia, and the results show BCR/ABL fusion gene with a cut point in the M-BCR region, which confirms the diagnosis of chronic myeloid leukemia. In this case we detail the importance of taking hematological disorders into consideration in the differential diagnosis of patients with otoneurological symptoms, and we also review the etiopathogenic mechanisms, symptoms, diagnosis, and therapeutic options for chronic myeloid leukemia with sudden hearing loss and vertigo.